A Systematic Literature Review of Hybrid Working: Trends, Challenges, and Future Directions - Kusuma, Alan Budi; Aprillia, Frida; Safria, Dhuha; Purwatiningsih, Purwatiningsih (Jurnal Multidisiplin Sahombu, 2025)
The rapid advancement of digital technology and the post-pandemic transformation of work have accelerated the adoption of hybrid working as a flexible model that combines remote and on-site work arrangements. This study aims to systematically review and analyze the existing body of research on hybrid working in order to identify key trends, research gaps, and future directions. A Systematic Literature Review (SLR) method was employed to synthesize prior studies and to evaluate the theoretical and practical implications of hybrid working for organizational productivity, employee well-being, and management practices. Complementing the SLR, a bibliometric analysis using VOSviewer and data from the Scopus database was conducted to map the distribution of publications, collaboration patterns, and scholarly impact within this research domain. The results indicate that research on hybrid working has expanded significantly since the COVID-19 pandemic, with a primary focus on digital transformation, employee engagement, and work–life balance. However, notable gaps remain, particularly in studies addressing leadership adaptability, organizational culture transformation, and the long-term sustainability of hybrid work models. Overall, the findings provide a comprehensive overview of the evolution of hybrid working research and offer valuable insights for policymakers, organizational leaders, and scholars seeking to design effective, inclusive, and sustainable hybrid work systems.